2005
DOI: 10.1128/aem.71.11.7327-7333.2005
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Extracellular Polysaccharides in Desiccation and Freezing Tolerance in the Terrestrial Cyanobacterium Nostoc commune

Abstract: The cyanobacterium Nostoc commune is adapted to the terrestrial environment and has a cosmopolitan distribution. In this study, the role of extracellular polysaccharides (EPS) in the desiccation tolerance of photosynthesis in N. commune was examined. Although photosynthetic O 2 evolution was not detected in desiccated colonies, the ability of the cells to evolve O 2 rapidly recovered after rehydration. The air-dried colonies contained approximately 10% (wt/wt) water, and field-isolated, natural colonies with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
255
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(265 citation statements)
references
References 20 publications
5
255
1
4
Order By: Relevance
“…PCC 7120 cells desiccated for 1 h seemed to be interlinked. Reduced O 2 evolution during 1 h of desiccation and an increased Chl a content are in line with those reported for Nostoc commune (Tamaru et al 2005). Phycocyanin is the predominant energy collectors of PS II, and once degraded, energy transfer to PSII gets impaired, as can be evident from decreased O 2 evolution in present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PCC 7120 cells desiccated for 1 h seemed to be interlinked. Reduced O 2 evolution during 1 h of desiccation and an increased Chl a content are in line with those reported for Nostoc commune (Tamaru et al 2005). Phycocyanin is the predominant energy collectors of PS II, and once degraded, energy transfer to PSII gets impaired, as can be evident from decreased O 2 evolution in present study.…”
Section: Discussionsupporting
confidence: 92%
“…Cyanobacterial cells were desiccated for pre-determined durations and the dried biomass (10 mg) used to measure oxygen evolution as described by Tamaru et al (2005). Rehydration of biomass was done in an oxygen electrode chamber (Rank Brothers, Cambridge, U. K.) with 25 mM HEPES-NaOH buffer (pH 7.0) supplemented with 10 mM NaHCO 3 .…”
Section: Oxygen Evolution Measurements In Rehydrated Cellsmentioning
confidence: 99%
“…Cyanobacteria such as Chroococcidiopsis and Nostoc species are able to survive with minimal water by synthesizing both internal and external polysaccharides (Warren-Rhodes et al, 2013;Smith et al, 2014). Tamaru et al (2005) indicated that the desiccation tolerance of Nostoc commune is strongly associated with extracellular polymeric substances (EPS). They removed the EPS from N. commune cells by homogenizing colonies with a blender and filtering through a coarse filter paper, and showed that cells depleted in EPS were highly sensitive to desiccation.…”
Section: Potential Of Cyanobacterial Metabolites As Moisturizersmentioning
confidence: 99%
“…They removed the EPS from N. commune cells by homogenizing colonies with a blender and filtering through a coarse filter paper, and showed that cells depleted in EPS were highly sensitive to desiccation. The hydrophilic/hydrophobic characteristics of EPS enable it to trap and accumulate water, and retard water loss during periods of desiccation (Tamaru et al, 2005). Li et al (2011) showed that Nostoc commune EPS has strong moisture-absorption and retention capacities compared with chitosan (a hygroscopic agent) and urea (a humectant).…”
Section: Potential Of Cyanobacterial Metabolites As Moisturizersmentioning
confidence: 99%
“…Nostoc cells experience extremes of desiccation, of which the water content is 0.02 to 0.05 g water cell solid -1 , approximately one order of magnitude lower than that of eubacterial spores (0.21 to 0.58) [27]. The mechanisms involved in the desiccation tolerance of Nostoc have been investigated using ecophysiology, biochemistry, and molecular biology [13,30,31,36]. However, the stability and biophysical properties of macromolecules inside desiccated cells are still poorly understood.…”
mentioning
confidence: 99%